Single-cell transcriptomics of bronchoalveolar lavage reveals divergent macrophage subpopulations and trajectories in interstitial lung disease - Lai-Ying Zhang; Peter C. Allen; Viviana P. Lutzky; Simon H. Apte; Penny L. Groves; Maxine E. Tan; Tharushi De Silva; Eleanor R. Spenceley; Rachael A. McCloy; Quan H. Nguyen; Joseph E. Powell; Daniel C. Chambers; et al. (PLoS ONE, 2026)
Rationale Interstitial lung diseases (ILDs) encompass a diverse range of fibrotic conditions and contribute to significant respiratory morbidity and mortality. Assessment of the cellular composition of bronchoalveolar lavage (BAL) fluid is an important diagnostic test in people presenting with ILD, but BAL cellularity remains relatively uncharacterized at single-cell resolution. Objective To characterize immune cell populations in BAL across different ILDs and investigate the impact of shortened peripheral blood leukocyte telomere length on BAL immune profiles. Methods Single-cell RNA sequencing and downstream analysis were performed on BAL samples from 24 male patients with various ILDs, including idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis, sarcoidosis, and silicosis. Both normal-telomere and short-telomere patients were included. Additionally, we integrated our findings with IPF genome-wide association study (GWAS) data. Results We identified sixteen distinct cell populations in BAL with notable differences across ILD subtypes. Analysis revealed six monocyte-like macrophage (MLM) subclusters following divergent trajectories: inflammatory CXCL10 hi MLMs predominated in hypersensitivity pneumonitis, while pro-fibrotic SPP1 hi MLMs were significantly expanded in IPF. Short-telomere patients showed a trend toward increased proportion of pro-fibrotic SPP1 hi MLMs, with enhanced expression of fibrotic genes compared to patients with normal telomere length. Integration with genomic data confirmed that SPP1 hi and CCL2 hi MLM subclusters harbour cells with the highest IPF disease relevance scores. Conclusion BAL-derived transcriptomics reveals distinct myeloid subpopulations across ILD subtypes, with specific populations associated with disease pathogenesis. These findings provide insight into ILD pathogenesis, motivate the development of more sophisticated diagnostic tests using BAL sampling, and highlight specific myeloid subpopulations as potential therapeutic targets.